Chemical Pressure‐Induced Unconventional Band Convergence Leads to High Thermoelectric Performance in SnTe - Hongwei Ming; Zhong‐Zhen Luo; Zhigang Zou (Advanced Science)
Abstract Band convergence is considered a net benefit to thermoelectric performance as it decouples the density of states effective mass (md∗) and carrier mobility (µ) by increasing valley degeneracy. Unlike conventional methods that typically prioritize md∗ at the expense of µ, this study theoretically demonstrates an unconventional band convergence strategy to enhance both md∗ and µ in SnTe under pressure. Density functional theory calculations reveal that increasing pressure from 0 to 5 GPa moves the Σ‐band of SnTe upward, reducing the energy offset between L‐ and Σ‐band from 0.35 to 0.2 eV while preserving the light band feature of the L‐band. Consequently, a high power factor (PF) of 119.2 µW cm−1 K−2 at 300 K is achieved for p‐type SnTe under 5 GPa. Chemical pressure also induces conduction band convergence, significantly enhancing the PF of n‐type SnTe. Additionally, the interplay between pressure‐induced phonon modes leads to a moderate increase in lattice thermal conductivity of SnTe below 3 GPa, which combined with the significantly enhanced PF, contributes to a large enhancement in ZT. Consequently, predicted ZT values of 2.12 at 650 K and 2.55 at 850 K are obtained for p‐ and n‐type SnTe, respectively, showcasing substantial performance enhancements.